2011
DOI: 10.1016/j.rmed.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viral upper respiratory tract infection on the urge-to-cough sensation

Abstract: Our results demonstrate that the UTC sensation is transiently enhanced during URI. We also confirm the results of the lone previous study that demonstrated transient enhancement of cough reflex sensitivity during URI. The UTC threshold may represent an additional relevant end point to measure in future studies evaluating potential antitussive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 8 publications
0
38
0
3
Order By: Relevance
“…Subsequent studies have mostly assessed influences on the intensity of experimentally induced urge-to-cough. For example, viral upper respiratory tract infections and nicotine withdrawal in smokers [10,11] appear to enhance the urge-to-cough, whereas it can be depressed by exercise [12] and mindfulness relaxation techniques [13]. However, none of these studies have acknowledged or reported the somatic sensations evoked by inhaled irritants, only the compulsion to cough.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have mostly assessed influences on the intensity of experimentally induced urge-to-cough. For example, viral upper respiratory tract infections and nicotine withdrawal in smokers [10,11] appear to enhance the urge-to-cough, whereas it can be depressed by exercise [12] and mindfulness relaxation techniques [13]. However, none of these studies have acknowledged or reported the somatic sensations evoked by inhaled irritants, only the compulsion to cough.…”
Section: Introductionmentioning
confidence: 99%
“…This cough hypersensitivity syndrome has also been defined as a clinical syndrome characterised by troublesome coughing often triggered by low levels of thermal, mechanical or chemical stimuli [22 ]. It is likely that acute cough resulting from an upper respiratory tract viral infection can be defined by a cough hypersensitivity because an increase in cough responses and urge-to-cough to inhaled capsaicin has been reported [23,24]. In addition, such a cough can in a proportion of subjects last for many months or years.…”
Section: Cough Hypersensitivity Syndromementioning
confidence: 99%
“…Stimulus-response functions for urge-to-cough are typically derived using doubling doses of tussive substances. The lowest dose required to elicit a detectable urge-to-cough has been dubbed the urge-to-cough threshold, or Cu (Dicpinigaitis et al, 2011). The relatively recent appearance in the literature of Cu measures reflects the growing interest in the sensation, and complements the traditional motor-related thresholds such as the C2 and C5, which are the lowest doses of a tussive stimulus that elicit two or five coughs (Choudry and Fuller, 1992).…”
Section: Sensory Attributes Of the Urge-to-coughmentioning
confidence: 99%